Investigating the effect of digitally augmented toys on young children's social pretend play. Issue 3 (3rd July 2019) - Hong, Jiwoo; Ko, Donghyeon; Lee, Woohun
ABSTRACT: This paper takes an interaction design approach to explore how children perceive augmented toys, assign symbolic meaning, and perform pretence socially in technology-mediated playing. We developed a system with three kinds of toys—each with distinct abstract appearances and audiovisual augmentation—based on several design decisions. An observational user study with thirty-two young children aged 3–7 years revealed that children utilized digital augmentation as a facilitator of pretending behaviour with the possibility for subjective interpretation while substituting an object for another. Digital augmentation was not only a social cue for children to respond by gathering together and negotiating socially for mutual pretence—it was also a hindrance by amplifying conflicts in a shared space. Our study empirically clarifies children's cognition and behaviour in an interactive system for pretend play and provides broader insight for the design of an interface enriching symbolic interpretation and social interaction.